Plasmon Enhanced Emission of Perovskite Quantum Dot Films - Dadi, Seyma; Altintas, Yemliha; Beskazak, Emre; Mutlugun, Evren; Dadl, Seyma; Altlntas, Yemliha (Cambridge Univ Press, 2018)
We propose and demonstrate the photoluminescence enhancement of CsPbBr3 perovskite quantum dot films in the presence of Au nanoparticles. Embedded into a polymer matrix, Au nanoparticle-quantum dot film assemble prepared by an easy spin coating method enabled the photoluminescence enhancement of perovskite quantum dot films up to 78%. The properties of the synthesized perovskite QDs and gold nanoparticles have been analysed using high resolution transmission electron microscopy, X-ray diffraction, energy dispersive X-ray spectroscopy, UV-Vis absorption spectrophotometer, steady state and time-resolved photoluminescence spectrometer.
Mutlugun, Evren/0000-0003-3715-5594
Keywords: Nanoscale; Optical Properties; Luminescence